Ecological response of Cedrus atlantica to climate variability in the Massif of Guetiane (Algeria) - Slimani, Said; Derridj, Arezki; Gutierrez, Emilia (Forest Systems, 2014)
Aim of the study: The study analyzes the long-term response of Atlas cedar, Cedrus atlantica (Manneti), to climate variability. Area of study: Atlas cedar forest of Guetiane (Batna, Algeria). Material and methods: The dendrochronological approach was adopted. An Atlas cedar tree-ring chronology was established from twenty trees. The response of the species to climate variability was assessed through the pointer years (PYs), the common climate signal among the individual chronologies, expressed by the first component (PC1), the mean sensitivity (msx), and response function and correlations analysis involving the tree-ring index and climate data (monthly mean temperature and total precipitation). Results: The highest growth variability was registered from the second half of the 20th century. The lower than the mean PYs, the PC1, and the msx increased markedly during the studied period. Dramatic increases in the PC1 and msx were detected at the end of the 1970s, reflecting a shift towards drier conditions enhancing an increasing trend towards more synchronous response of trees to climate conditions. The response function and correlations analysis showed that tree growth was mainly influenced by precipitation variability. Research highlights: Our findings provide baseline knowledge concerning the ecological response of Atlas cedar to climate variability in in its southern distribution limit, where a high level of tree mortality has been observed during recent decades, coinciding with the driest period Algeria has ever experienced. This information is vital to support ongoing ecosystem management efforts in the region. Keywords: Atlas cedar; annual growth variability; dieback; dendrochronology.